Current research on the application of membrane distillation technology in industrial wastewater treatment: A review - N. A. S., Muhamad; Nadzirah, Mohd Mokhtar; Rosmawati, Naim; W. J., Lau; Ahmad Fauzi, Ismail (2022)
Membrane distillation (MD) is an emerging technology for separations and purifications that claims to be a cost-effective separation process, has high removal capacity and flexibility of operation. As an attractive separating process, MD has been the subject of worldwide academic studies. Unfortunately, from the commercial standpoint, MD has gained only little acceptance and yet to be implemented in industry. The purpose of this review is to provide an overview of the recent applications of MD in treatment of industrial wastewater in order to obtain clean water and to recover valuable compounds. Besides, the limitation encountered during MD process including membrane fouling, membrane pore-wetting, thermal polarization, concentration polarization and energy consumption were also discussed.